(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Picrorhiza kurroa is an important medicinal herb in traditional ayurvedic and Tibetan medicine. It has been used for centuries to treat a variety of diseases, including liver disease. Present studies have suggested that Picrorhiza kurroa have potential as a therapeutic agent for treating Isoniazid−rifampicin. Isoniazid-rifampicin is anti-tubercular that is commonly used in industrial and laboratory settings. Exposure to Isoniazid-rifampicin can cause damage to the liver, resulting in severe liver diseases. The protective effect of Picrorhiza kurroa root and leaves on INH and RFP-induced liver injury involve regulating multiple pathways. The results of the Picrorhiza kurroa root and leaves show the prevention and treatment of the Isoniazid−rifampicin -induced liver injury. In addition, antioxidant also plays a critical role in the treatment of Isoniazid−rifampicin -induced liver injury. However, Picrorhiza kurroa root and leaves have both antioxidant and pro-oxidative effects. High-dose of Picrorhiza kurroa root and leaves (200 mg/kg) may act as a pro-oxidant and cause oxidative stress as compared to lower dose with promising action. The protective effect of Picrorhiza kurroa root and leaves on Isoniazid−rifampicin -induced livery injury were presented in this work. Further research should be carried out to discover novel solutions for preventing and treating Isoniazid−rifampicin-induced liver injury and the detailed molecular mechanisms involved in Picrorhiza kurroa root and leaves protective effect.